Ethical thinking in cyber resilience: lessons from Malaysian cyber leaders - Abdul Molok, Nurul Nuha; Zulkifli, Zahidah; Jeong, Jongkil Jay; Maynard, Sean; Ahmad, Atif (Springer, 2025)
This study explores the intersection of ethical thinking and cyber resilience within the context of Malaysian government agencies. Given the increasing reliance on digital infrastructure and the rising threat of cyber-attacks, the need for robust cyber resilience strategies developed by people who are imbued with ethical values, is more critical than ever. However, the role of ethical considerations in shaping these strategies remains underexplored, especially in the public sector. Through a qualitative approach employing interviews as the primary data collection method and thematic analysis as the method for qualitative data analysis, this research proposes the importance of ethics in developing Malaysia’s cyber resilience. From the analysis, 4 themes have been identified: moral and spiritual beliefs, alignment to the government agenda, responsibility, and long-term thinking. Findings suggest that ethical thinking plays a crucial role in decision-making processes which influence the development and implementation of cyber-related strategies, policies, and law in Malaysian public sector organisations. This study proposes the integration of ethics in the development of national cybersecurity strategies, to make the country more resilient to protect itself against cyber threats.